Flap your wings - Eastman, Philip D. 1909-1986 (Beginner books : I can read all by myself, 2000)
When a strange egg appears in their nest, Mr. and Mrs. Bird kindly take it upon themselves to raise the "baby bird" inside. But when the egg hatches, the Birds are in for a big surprise--"Junior" is the oddest-looking baby bird they've ever seen--with big, long jaws full of teeth and an appetite to match. In fact, he looks more like a baby alligator than a baby bird! Nevertheless, the devoted Birds run themselves ragged feeding Junior until he gets so big, he must leave the nest or it will collapse underneath him. But how can Junior fly without wings? To the delight of the Birds--and readers!--the dilemma is solved when Junior takes off from a branch overlooking a pond